2017
DOI: 10.1007/s10787-017-0325-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of co-administration of pregabalin and vitamin E on neuropathic pain induced by partial sciatic nerve ligation in male rats

Abstract: Our results showed antinociceptive effects of both vitamin E and pregabalin alone or in combination in PSNL rats and also neuroprotective properties without affecting locomotor activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…To date, there is no published evidence about the antiallodynic interaction between pregabalin + thioctic acid, but a clinical trial has been registered to compare both drugs alone, or in combination, in the treatment of several pathologies of neuropathic pain in subjects (Gilron et al, ). Our data about the antiallodynic effect of pregabalin + α‐tocopherol combination agrees with a study performed in rats submitted to partial sciatic nerve‐ligation that indicates that tocotrienol shows a tendency to increase slightly the antineuropathic effect of pregabalin (Meymandi et al, ). Likewise, they are in line with a randomized controlled clinical trial, where vitamin E seems to improve the total pain score of diabetic patients treated with pregabalin and hypoglycemic agents (Rajanandh et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…To date, there is no published evidence about the antiallodynic interaction between pregabalin + thioctic acid, but a clinical trial has been registered to compare both drugs alone, or in combination, in the treatment of several pathologies of neuropathic pain in subjects (Gilron et al, ). Our data about the antiallodynic effect of pregabalin + α‐tocopherol combination agrees with a study performed in rats submitted to partial sciatic nerve‐ligation that indicates that tocotrienol shows a tendency to increase slightly the antineuropathic effect of pregabalin (Meymandi et al, ). Likewise, they are in line with a randomized controlled clinical trial, where vitamin E seems to improve the total pain score of diabetic patients treated with pregabalin and hypoglycemic agents (Rajanandh et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…PGB pretreatment of VPA‐induced autism‐like symptoms increased TDM and speed similar to control values. In several studies, it was shown that PGB did not affect motor activity (Meymandi, Sepehri, et al, 2017; Zimcikova, Simko, Karesova, Kremlacek, & Malakova, 2017), on the contrary, neuroprotective effect of PGB may contribute in the improvement of motor activity in all prenatally exposed PGB groups (Salat et al., 2016; Shamsi Meymandi et al., 2018). However, a recent study reported that PGB at high doses of 600 mg/kg might produce defect in chick embryos (Sayin & Simsek, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…PGB treatment during gestational period was associated with beneficial effects on distorted pain sensitivity in prenatally VPA exposed rats, that is, low dose of PGB treatment (15 mg/kg) during gestational period in prenatally VPA‐treated rats significantly decreased the threshold to pain stimuli (in tail flick) compared to VPA group. In fact, PGB showed antinociceptive effect in different animal models of acute and chronic pain in normal rats (Meymandi & Keyhanfar, 2012; Meymandi, Keyhanfar, Sepehri, Heravi, & Yazdanpanah, 2017; Meymandi, Keyhanfar, Yazdanpanah, & Heravi, 2015; Meymandi, Sepehri, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vit E, a free scavenger, reduces oxidative‐nitrosative stress 12 . It has been reported to reduce hyperalgesia and allodynia effects of NP 13‐15 via its antioxidant and anti‐inflammatory properties 12,16 . LiCl, a common bipolar disorder drug, possesses anti‐allodynic and anti‐hyperalgesic properties against various models of NP 17‐19 .…”
Section: Introductionmentioning
confidence: 99%